2009
DOI: 10.2746/042516408x345134
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective multicentre study of methicillin‐resistant Staphylococcus aureus infections in 115 horses

Abstract: These results should help direct future research with regard to investigation of risk factors for equine MRSA infection in community and hospital populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
50
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(55 citation statements)
references
References 33 publications
5
50
0
Order By: Relevance
“…These results could have a potential clinical use, since these autologous substances could be used as prophylactic or therapeutic antibacterial biodrugs in several situations including soft tissue and orthopaedic equine surgery, or for the treatment of local infections (i.e. : septic arthritis or synovitis and abdominal or other incisional wounds) produced by MRSA (Anderson et al 2009). However, clinical and experimental studies should be performed to know the real therapeutic potential of these cellular blood products (ePC or PPP) in equine practice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results could have a potential clinical use, since these autologous substances could be used as prophylactic or therapeutic antibacterial biodrugs in several situations including soft tissue and orthopaedic equine surgery, or for the treatment of local infections (i.e. : septic arthritis or synovitis and abdominal or other incisional wounds) produced by MRSA (Anderson et al 2009). However, clinical and experimental studies should be performed to know the real therapeutic potential of these cellular blood products (ePC or PPP) in equine practice.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a study conducted in 206 horses with septic synovitis reveled that 23 horses (34.3%) were positive for Staphylococcus aureus of which 7 (30.3%) were subjected to euthanasia by the non-resolution of the infection (Taylor et al 2010). However, these infections could potentially be more grave when produced by MRSA strains, although this situation has not been fully proven in horses (Anderson et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that MRSA has been frequently isolated from unhealthy horses, transmitted between animals and humans [1,33,36,37]. A high prevalence of methicillin-resistant staphylococci (MRS) colonization has also been reported in healthy horses in Europe [2,4,9,20,34] and Japan [38,39].…”
mentioning
confidence: 99%
“…Residence on a farm that housed more than 20 horses was a factor significantly associated with MRSA colonization [63]. In a retrospective multicentre study investigating MRSA infections in 115 horses, previous hospitalization and treatment with gentamicin were associated significantly with CA-MRSA, whereas infected incision sites were associated significantly with HA-MRSA [61].…”
Section: Risk Factors For Colonization and Infection In Horsesmentioning
confidence: 99%
“…To date, MRSA has been isolated from horses in Europe, Asia and North America [53][54][55][56][57][58][59][60]. Wound and post-operative infections with MRSA tend to be most common [1,61].…”
Section: Occurrence In Horsesmentioning
confidence: 99%